The Paradigm Examples of Polar Concept in Shakespeareas Hamlet (Global Journal of Human-Social Science, 2012)
The present article tries to make a fresh analysis of Shakespeare s touchstone Hamlet taking into consideration the term polar concept argument Polar concept is a postmodern hermeneutical form of reading and analyzing texts which sprung from the mind of the British philosopher and critic Gilbert Ryle Polar concept as a reading strategy is a kind of argument that affirms the understanding of one concept from the mere understanding of its polar opposite English literature is replete with write-ups that tackle readers in a dilemmatic situation and this has always caused the dualistic concepts to come to the fore however in a polar concept strategy understanding occurs because the existence of one concept paves the way for its contrary and consequently leads to a dialectical monism The polar concept as a literary term has played a very crucial role in Shakespeare s Hamlet therefore this study is an attempt to highlight the polarity of different concepts in this tragedy The author believes that by drawing a paradigm of polar concepts throughout Hamlet or any other text readers would be able to enjoy different levels of meanings without being petered out by the dexterity of literary devices andtropes
Keywords: Hamlet; Polar concept; Meaning; Balance